Framing Gibran Rakabuming Raka: A Media Analysis of CNN Indonesia's Coverage of His Vice-Presidential Nomination - Qirom, Rizqi Latiful; Wibowo, Arif Ardy; Nasir, Roziani (CHANNEL: Jurnal Komunikasi, 2024)
Indonesia will celebrate democracy in 2024. In order to nominate candidates for president and vice president of Indonesia between 2024 and 2029, a coalition of several political parties will be formed. Prabowo Subianto and his running mate, Gibran Rakabuming Raka, are among the presidential candidate pairings being promoted. However, because of his youth and PDI Perjuangan party connection, Gibrans's nomination as a vice presidential candidate generated a range of public reactions. The PDI Perjuangan has formally announced Ganjar Pranowo and Mahfud MD as their candidates for the next Indonesian presidential election. Other media channels, such as CNN Indonesia, have taken notice of Gibran's situation and have included large headlines and in-depth coverage on their websites. Gibran's coverage aims to clarify his role as Prabowo Subianto's running mate for vice president and as a member of the PDI Perjuangan party. The purpose of this study is to examine how Gibran's reputation was built within CNN Indonesia following his unsuccessful bid for vice president. The study used a case study approach and a descriptive qualitative methodology. The Zhongdang Pan and Gerald M. Kosicki framing analysis model, which identifies media with syntactic, script, thematic, and rhetorical structures, was used to analyze the CNN Indonesia media. According to the statistics, CNN Indonesia developed Gibran's viewpoint by taking into account a variety of viewpoints from other people. None of the four news stories that were examined contained a resignation letter explaining Gibran's reason for leaving the PDI Perjuangan cadre.